2019
DOI: 10.1159/000496296
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life 10 Years after Sleeve Gastrectomy: A Multicenter Study

Abstract: Objective: Sleeve gastrectomy (SG) has recently become the most commonly applied bariatric procedure worldwide. Substantial regaining of weight or severe reflux might compromise quality of life (QOL) after SG in the long-term follow-up. Long-term data on patients’ QOL is limited, even though the persistent improvement in QOL is one of the aims of bariatric surgery. The objective of this study was to present patients’ QOL 10 years after SG. Methods: Of 65 SG patients with a follow-up of ≥10 years after SG who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Additionally, erosive esophagitis was even more prevalent in the presence of HH, affecting around half of patients after SG, and also irrespective of PPI treatment. These findings are partially in line with aforementioned data 19,34,36,64 . Furthermore, while stenosis, ulcers, or pylorospasms can be identified by UGD, twisting, kinking, functional stenosis, and cicatrization may remain undetected 46 .…”
Section: What Are the Treatment Options For Gerd Following Sg?supporting
confidence: 86%
See 2 more Smart Citations
“…Additionally, erosive esophagitis was even more prevalent in the presence of HH, affecting around half of patients after SG, and also irrespective of PPI treatment. These findings are partially in line with aforementioned data 19,34,36,64 . Furthermore, while stenosis, ulcers, or pylorospasms can be identified by UGD, twisting, kinking, functional stenosis, and cicatrization may remain undetected 46 .…”
Section: What Are the Treatment Options For Gerd Following Sg?supporting
confidence: 86%
“…17,18 GERD is the major cause of impaired quality of life after bariatric surgery and may be associated with a decrease in physical functioning as well as an increase in mental and emotional problems, resulting in poorer social functioning. 19,20 Owing to these potentially severe consequences, GERD still remains the most common reason for revisional surgery after SG. 10 However, assessing the impact of GERD in general and after SG in particular is challenging owing to the lack of standardized reporting and varying definitions.…”
Section: How Frequent Is Gerd After Sg?mentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a generic questionnaire precluded comparisons with QOL in the general population. Cross-sectional reports on generic QOL using the Short Form 36 Health Survey (SF-36) 5 years after SG are published 10–12. Comparing two similar cohorts of patients before and 5 years after surgery, we reported that mean SF-36 scores were significantly higher in the 5-year cohort than in the baseline cohort, although still below the general population norm 12.…”
Section: Introductionmentioning
confidence: 97%
“…While SG scored better in many parameters, re ux und weight regain are still matter of discussion by many authors when looking on the long-term follow up. Felsenreich et al found that EWL and symptomatic re ux impair patients' long-term quality of life after SG [19]. This observation should be taken into account when choosing the type of bariatric surgery for the individual patient.…”
Section: Discussionmentioning
confidence: 99%